Membangun Kepercayaan Konsumen untuk Meningkatkan Intensi Pembelian - Ida Bagus Nyoman Udayana; Aria Pramana (University of Merdeka Malang, 2019)
The aim of this research is to examine how to build consumer trust to increase purchase intention in the case study of the SoWellShop online store through testing the effect of ability, benevolence of business and integrity on customer trust and testing the effect of customer trust on purchase intention. The sampling method is non-probability, and the sampling technique uses purposive sampling. Data collected through questionnaires given to 100 respondents. The data analysis uses regression.. The results show that: 1) ability, benevolence of business, and integrity have a significant and positive effect on customer trust, 2) the customer trust has a significant and positive effect on the purchase intention variable.https://doi.org/10.26905/jmdk.v7i2.3039